1998
DOI: 10.1038/1243
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2 macroglobulin is genetically associated with Alzheimer disease

Abstract: Alpha-2-macroglobulin (alpha-2M; encoded by the gene A2M) is a serum pan-protease inhibitor that has been implicated in Alzheimer disease (AD) based on its ability to mediate the clearance and degradation of A beta, the major component of beta-amyloid deposits. Analysis of a deletion in the A2M gene at the 5' splice site of 'exon II' of the bait region (exon 18) revealed that inheritance of the deletion (A2M-2) confers increased risk for AD (Mantel-Haenzel odds ratio=3.56, P=0.001). The sibship disequilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
276
5
13

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 613 publications
(304 citation statements)
references
References 29 publications
6
276
5
13
Order By: Relevance
“…Previous studies have indicated that there may be alterations in the levels of proteins that attenuate Ab fibrillization, namely a2M 155 and SAP 156 in AD patients, although there are also conflicting data on this issue. It should be noted that polymorphism in the a2M gene may be associated with AD risk in some populations and may be influenced by family history (for example references [157][158][159][160][161][162] ), although these findings are controversial. Decreased SAP levels have also been correlated with impaired cognitive performance in aged individuals 163 and in clinically diagnosed AD.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
“…Previous studies have indicated that there may be alterations in the levels of proteins that attenuate Ab fibrillization, namely a2M 155 and SAP 156 in AD patients, although there are also conflicting data on this issue. It should be noted that polymorphism in the a2M gene may be associated with AD risk in some populations and may be influenced by family history (for example references [157][158][159][160][161][162] ), although these findings are controversial. Decreased SAP levels have also been correlated with impaired cognitive performance in aged individuals 163 and in clinically diagnosed AD.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
“…Two candidate genes in the region, alpha-2-macroglobulin (A2M [MIM 103950]) and the low-density lipoprotein receptor-related protein (LRP1 [MIM 107770]), have been the target of investigations, but without consistent results. 16,36,[42][43][44][45] Saunders et al, 46 using the larger NIMH samples, identified several haplotypes that showed an association with AD, suggesting that there may be a gene-either A2M or one nearby-that may confer a modest effect toward AD.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence indicated that additional risk genes exist on chromosome 12 for AD (Blacker et al 1998;Hollenbach et al 1998;Poduslo and Yin 2001;LuedeckingZimmer et al 2003;Beecham et al 2009). The VDR gene is very close to this region and our earlier study provided the first evidence for a possible genetic association between AD and VDR (Gezen-Ak et al 2007).…”
Section: Discussionmentioning
confidence: 99%